Exploration of Unani concept of blood purifying drugs and likely models for its screening - Mushir, Ansari; Jahan, Nasreen; Sofi, Ghulamuddin (Bangladesh Journal of Medical Science, 2019)
Introduction: In Unani system of medicine, blood is regarded as mixture of akhlat (humours) i.e. dam (Sanguine), balgham (phlegm), safra (yellow bile) and sawda (black bile). Normal blood consists of “akhlate latifa (plasma)” and “kaseefa (corpuscles)”. Normal blood is one in which all humours are in normal proportion in terms of quantity and quality and specific to each individual. It is normal in colour, free from bad odour and moderate in viscosity. Morbid blood develops due to impurities /disease in the blood which ultimately alter its quantity and quality. If we co relate these abnormalities with modern concept then all bleeding disorders and coagulopathy fall under “Riqqate dam” (low viscosity of blood); all the thromboembolic disorders; polycythaemia, leukaemia and anaemia fall under “Ghilzate dam”(hyperviscosity of blood), while septicaemia, bacterial diseases can be correlated with “ufunat” (infections). Methods: The classic and relevant books of Unani and conventional medicine were studied. The databases utilized for obtaining information, are scientific research publications from indexed journals available through Google Scholar, PubMed and Science Direct. Results and Conclusion: Blood purifying drugs cause necessary changes and maintain the viscosity of the blood by their moderate heat; cold; dry and wet properties. These drugs are alterative and bring the quality and quantity of blood in equilibrium. Strengthen the defensive mechanism and eliminate toxins via sweat, urine, faeces etc. These drugs are digestive, tonic to stomach and liver and boost the immune system. In the line of the above conceptual framework few experimental models are being suggested i.e. effect of drugs on blood constituents, coagulation parameters, anemia, leukaemia, polycythaemia, thrombocytopenia and infections. This preliminary study may serve as a tool for the screening of blood purifier drugs in various blood disorders. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.312-321